Phenocopies in melanoma-prone families with germ-line CDKN2A mutations. (September 2018) - Helgadottir, Hildur; Olsson, Håkan; Tucker, Margaret; Yang, Xiaohong; Höiom, Veronica; Goldstein, Alisa
Abstract Purpose Carriers ofCDKN2A mutations have high risks of melanoma and certain other cancers. In this study we examined the occurrence of tumors amongCDKN2A wild type (wt) members of melanoma-prone families withCDKN2A mutations. Methods Swedish and US melanoma-prone families withCDKN2A mutations were included. Data was collected on tumors diagnosed among family members. Among theCDKN2A mutated families, members withCDKN2A wt status who were diagnosed with melanoma were designated phenocopies. Results Of patients with melanoma in theCDKN2A mutated families (n  = 266), 7.1%, were seen among members withCDKN2A wt status (phenocopy rate). Among theCDKN2A wt family members of theCDKN2A mutated families (n  = 256), 7.4% were diagnosed with melanoma. The prospective relative risk for melanomas was significantly higher among theCDKN2A wt subjects compared with population-based controls (7.4 (95% confidence interval 1.7–33.2)), while no elevated risks of nonmelanoma cancers were seen and their offspring did not have significantly elevated risks of melanoma or other cancers. Conclusion Members ofCDKN2A mutation carrying families who test negative for their family's mutation have moderately increased risk for melanoma and should, in addition to being considered for continuing dermatologic surveillance, be encouraged to follow sun safety recommendations and practice skin self-exams.